Gladstone and Nonconformity in the 1860s: The Formation of an Alliance - Machin, G. I. T. (The historical journal, 1974)
It is well known that Gladstone's progress to the leadership of the Liberal party between 1859 and 1868 included the building of an alliance with Nonconformity which lasted, wim some interruptions, to the end of his life. This coalition was remarkable in view of the previous diversity of viewpoint between its participants. In the 1830s Nonconformists had already adopted a policy of disestablishment when Gladstone was airing a diametrically opposite opinion in The State in its relations with the Church; and Gladstone's High Churchmanship was disliked by the evangelical Nonconformists, one of whom wrote a pamphlet entitled The Ritualistic Movement in the Church of England, a reason for disestablishment. In view of these differences, how did there develop a firm and continually reviving political alliance, as intimate as that between Gladstone and Irish Home Rulers in the 1880s?